Deployable Structures Based on Buckling of Curved Beams Upon a Rotational Input. (28th May 2021) - Mhatre, Saurabh; Boatti, Elisa; Melancon, David; Zareei, Ahmad; Dupont, Maxime; Bechthold, Martin; Bertoldi, Katia
Abstract: Inspired by the recent success of buckling‐induced reconfigurable structures, a new class of deployable systems that harness buckling of curved beams upon a rotational input is proposed. First, experimental and numerical methods are combined to investigate the influence of the beam's geometric parameters on its non‐linear response. Then, it is shown that a wide range of deployable architectures can be realized by combining curved beams. Finally, the proposed principles are used to build deployable furniture such as tables and lamp shades that are flat/compact for transportation and storage, require simple or no assembly, and can be expanded by applying a simple rotational input. Abstract : Buckling of curved beams upon a rotational input is utilized to design and fabricate reconfigurable structures. Through numerical simulations, key geometric parameters governing the non‐linear response of the beams are identified. The results are applied to realize deployable furniture that are flat/compact for transportation and storage and can be deployed into functional shapes by applying a simple rotational input.